HUBUNGAN KELOMPOK BELAJAR DENGAN PRESTASI BELAJAR SISWA (STUDI PADA KELOMPOK BELAJAR YANG DILAKUKAN OLEH SISWA KELAS XI IPS MAN 2 MODEL PEKANBARU) - Maessy Cahya AP; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research claim to ( 1) knowing group influence learn to Class XI IPS MAN Student achievement 2 Model Pekanbaru ( 2) knowing how big influence group learn to Class XI IPS MAN Student achievement 2 Model Pekanbaru. With respondent amount 84 divisible school student for 42 student have achievement and 42 group member student learn. This research have the character of korelasional which is mentioning with quantitative research of inferensial.By using test of correlation of Karl Pearson, in earning correlation (r) of equal to 0,074 is hereinafter by examination of determinasi obtained that is group learn to influence achievement of student of equal to 0.543%. Pursuant to test of hypothesis known that > so that hypothesizing rejected (0,474 > 0,2912) meaning there is relation of between group learn with achievement learn. Conclusion which is there are in statement of above that is there relation which signifikan between group learn with achievement learn but his relation is very weak, the rest of there are at other or dissimilar research which do not there are in this research.keywords: group learn, student of achievement learn, student of member group learn and achievement learn